A Survey of Book Production and Book Cultures in Early Medieval Britain (KULT_online, 2013)
Volume I of the series The Cambridge History of the Book in Britain covers aspects of book production and use from Roman Britain to the Norman Conquest. The emphasis of the 39 essays lies on outlining chronology and broad developments. Care has been taken to give a geographically balanced account of book cultures in Britain despite the lack of extant material from the Celtic realms and Wales. The result is a balanced, comprehensive, and considered survey on early books in Britain. An occasional break from the chronological survey of material – the highlighting of a particular book, for example, or presenting of findings from a theoretical or critical perspective – would have made the volume a more refreshing read.